Encyclopedia of GIS - Shekhar, Shashi 1963-.; Xiong, Hui.; Gale Group (New York Springer, 2008)
Entries explain the key software, data sets, and processes used by geographers and computational scientists. Includes major overviews on topics, such as geoinformatics, spatial cognition, and location-based services. Shorter entries define specific terms and concepts, such as the global positioning system, digital elevation/terrain model, and remote sensing.
Security and privacy in geospatial information systems -- Statistical modeling for spatial data -- Spatial database modeling for applications -- Spatial association discovery -- Digital road map -- Critical evaluation of standard proposals -- Geospatial semantic web -- Spatial thinking -- Emergency evacuations -- Information collection using sensor network -- Commercial GIS -- Spatio-temporal data modeling -- Spatial co-location rule mining -- GIS issues and applications -- Spatial prediction -- Basic concepts -- Commercial spatial databases -- Spatial uncertainty and imprecision -- Indoor positioning -- Evacuation planning and operations -- Spatial outlier detection -- Spatial data warehousing and decision support -- Photogrammetry -- Cartography and visualization -- Basic storage and retrieval structure -- Open source GIS software -- Geosensor networks -- Use of spatial data for simulation -- Tesselation data models -- Spatial aspects of bioinformatics -- Spatial constraint databases -- Spatial analysis -- Representation of inexact spatial information -- Road network databases -- GIS in business intelligence, routing -- Spatial indexing -- Spatio-temporal databases -- Spatial aspects of mobile computing -- Spatial aspects of distributed computing -- Spatial time series -- Data exchange and interoperability.
Electronic reproduction.
Keywords: Geographic information systems -- Encyclopedias; Information storage and retrieval systems -- Geography; Electronic books